2015
DOI: 10.1001/jamapediatrics.2015.0182
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Childhood Obesity Interventions in Pediatric Primary Care

Abstract: IMPORTANCE Evidence of effective treatment of childhood obesity in primary care settings is limited. OBJECTIVE To examine the extent to which computerized clinical decision support (CDS) delivered to pediatric clinicians at the point of care of obese children, with or without individualized family coaching, improved body mass index (BMI; calculated as weight in kilograms divided by height in meters squared) and quality of care. DESIGN, SETTING, AND PARTICIPANTS We conducted a cluster-randomized, 3-arm clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
131
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 91 publications
(136 citation statements)
references
References 32 publications
5
131
0
Order By: Relevance
“…29 A recent study provided evidence that the use of an electronic decision support system similar to the one used in the present study can be successful in improving BMI in children. 30 This study benefited from measured weight and height from medical office visits as opposed to self-reported weight and height. All children were members of a large prepaid managed care system, and standardized screening guidelines for weight and height in all children in the health plan were routine.…”
Section: Discussionmentioning
confidence: 99%
“…29 A recent study provided evidence that the use of an electronic decision support system similar to the one used in the present study can be successful in improving BMI in children. 30 This study benefited from measured weight and height from medical office visits as opposed to self-reported weight and height. All children were members of a large prepaid managed care system, and standardized screening guidelines for weight and height in all children in the health plan were routine.…”
Section: Discussionmentioning
confidence: 99%
“…14,22 These tools included pre-populated, standardized note templates specific for obesity that included options for: 1) documenting and coding for BMI percentile, 2) documenting and coding for nutrition and physical activity counseling, 3) placing referrals to weight management programs, 4) placing orders for laboratory studies if appropriate, and 5) printing educational materials.…”
Section: Methodsmentioning
confidence: 99%
“…These materials were based on our previous STAR trial and have been shown to be effective in improving child BMI. 14 The materials focus primarily on decreases in screen time and sugar-sweetened beverages; increases in moderate and vigorous physical activity; and improvement of sleep duration and quality. Based on our qualitative work with positive outlier families and feedback from our parent and youth advisory board, we also developed materials to promote social and emotional wellness.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations